MARKETING DALAM PERSPEKTIF EKONOMI ISLAM - Nur Fadilah (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2025)
It is the result of literature research that collects data from books, journals, and articles that discuss marketing from an Islamic economic point of view. The data collected were examined qualitatively descriptively. In the economic system, marketing, also known as marketing, is an important component that must be considered and done to achieve product sales targets in the hope that the business can achieve success. Some market players ignore marketing ethics to achieve business targets. In Islam, the Prophet has taught sharia business ethics, including marketing, through his nature called SAFT, which stands for "shiddiq, amanah, fathanah, and tabligh." In addition, people working in the field of marketing must pay attention to the ethical principles of Rabbani, Akhlaqiyyah, Realistic, and Humanistic. Marketing is prohibited in Islam, so no marketing harms people, especially customers and business partners